(untitled) (American Journal of Business Management, Economics and Banking, 2023)
In the article, the concepts of digitization of the economy and digital transformation of the economy are conceptually analyzed. The interrelationship and interdependence of these definitions are examined. The features of the digital transformation of the economy were analyzed and its main advantages were highlighted. The role of marketing in the digital transformation of the economy was studied. In the conditions of digital transformation, the analysis of the main factors of the marketing environment was carried out, and the factors of the formation of a fundamentally new environment were determined. Changes in marketing concepts used in the modern economy are studied. In the context of the digital transformation of the economy, new marketing concepts are proposed. Engagement marketing, personalized marketing, retrospective marketing. As a reaction to changes in the external environment and the economy as a whole, a proportion of new concepts of marketing are implemented.